Intermittent fasting-induced improving insulin resistance in healthy obese adults: A scoping review - Prabowo, Nyono Dedi (Indonesian Nutrition Association, 2024)
Background: Obesity is a severe global public health problem linked to chronic noncommunicable disease and increased mortality. It has harmful effects on metabolic disorders via the insulin resistance pathway. Available guidelines recommend caloric reduction via intermittent fasting for obesity management. However, the available literature is less focused on the benefits of intermittent fasting on improved insulin resistance in healthy obese adults, especially related to an accumulation of free fatty acids. Therefore, a scoping review is necessary. Objective: This review aims to collect evidence on the benefits of intermittent fasting on improved insulin resistance in healthy obese adults. Methods: This scoping review followed the 5-step Arksey and O'Malley framework and was submitted following PRISMA ScR. Five electronic databases were thoroughly searched. Papers are included if they are eligible. The result was a synthesis of descriptive and narrative elements. Results: 1117 papers were collected in total. Nine randomized controlled trial studies met the review's inclusion criteria. The papers included are sourced from reputable, relevant sources. As a whole, intermittent fasting appears to benefit improved insulin resistance in healthy obese adults. Intermittent fasting has been shown to reduce insulin levels while increasing insulin sensitivity, therefore improving insulin resistance. Conclusion: Evidence suggests that intermittent fasting can help improve insulin resistance in healthy obese adults.